The Influence of Work Motivation and Leadership Style on Employee Performance - Aesah, Siti; Suprapti, Endang; Hernawati, Sri Purni (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of work motivation and leadership style on employee performance at PT. Primafood International Kalisuren Poultry Kiosk, Bogor, either partially or simultaneously.The method used is quantitative with a sample of 85 people. Data analysis used validity test, reliability test, classic assumption test, linear regression analysis, correlation coefficient analysis, coefficient of determination and hypothesis testing. The results of the analysis show that motivation and leadership style have a significant positive effect on employee performance both partially and simultaneously.This research makes a new contribution by showing that motivation and leadership style have an important role in improving employee performance where these three variables have a strong relationship and great influence.